The effect of mindfulness training interventions on free throw performance in basketball players in stressful situations - Wang, Xiaotao; Zhang, Ziyun (Frontiers in Psychology, 2025)
ObjectiveTo explore the effect of mindfulness training interventions on the free throw performance of basketball players in stressful situations.MethodsA 2 (high stress, low stress) × 2 (mindfulness training, placebo) factorial design was used. Seventy-nine male college students majoring in basketball from universities, who had experience in provincial-level or above basketball competitions, were recruited and randomly divided into 4 groups. The mindfulness group received 8 weeks of mindfulness training, with 2 sessions per week and each session lasting 90 min, while the placebo group watched biographical videos of basketball figures during the same period. The Five Facets Mindfulness Questionnaire, the Chinese version of the Connor-Davidson Resilience Scale, and a specific free throw scoring method were used to measure mindfulness levels, mental toughness, and free throw performance before and after the intervention. Based on SPSS 25.0 software, statistical analyses were conducted using one-way analysis of variance, the linear response model of the Generalized Linear Model, and Pearson correlation analysis.ResultsMindfulness training significantly improved the mindfulness levels, mental toughness, and free throw performance of athletes (p < 0.05). There were significant positive correlations among mindfulness levels, mental toughness, and free throw performance (p < 0.05).ConclusionMindfulness training is helpful for improving the free throw performance of basketball players in stressful situations.